KHAWARIJ: ALIRAN-ALIRAN DAN PEMIKIRAN - Anas Nasrudin; Lesti Lestari; Adi Noviardi; Heri Setiaji (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
Khawarij thought has existed since the Prophet Muhammad was still around. The hadiths show this. However, the emergence of this group began when Ali Bin Abi Talib became Caliph and was involved in a conflict with Mu'awiyah who was the governor of Syria. The conflict occurred because Mu'awiyah demanded that Ali bin Abi Talib solve the Uthman bin Affan murder case. This conflict then led to a war called the Shiffin War and ended with an agreement to negotiate. After an agreement was reached, there were groups who were dissatisfied with the results of the agreement and they left and separated themselves. This group came to be known as the Khawarij. They fight against the legitimate government and spread ideas that deviate from the Qur'an and Sunnah.